Optimizing mental health: smartphone discharge planning's on impact on stroke survivor' mood - Retnaningsih, Dwi; Ramadhani, Desi; Suara, Eviwindha (Intelektual Pustaka Media Utama, 2025)
Stroke is a disease that causes a variety of physical and psychological disorders, resulting in limitations in a person's life. Stroke patients often experience psychological problems such as depression, anxiety, and stress as a result of changes in their life activities. Discharge planning is considered an intervention that can reduce complications and improve the quality of life of stroke patients. However, there are still reports that the implementation of discharge planning is not optimal, and one of the reasons is the use of inappropriate methods. The aim of the study was to demonstrate the impact of the use of discharge planning applications on the levels of depression, anxiety, and stress in stroke patients. The research method used is quasi-experimental quantitative research with a one-group pretest and posttest design. A total of 21 respondents used purposive sampling techniques. The results showed changes in levels of depression, anxiety, and stress after application-based discharge planning. The Wilcoxon statistical test results obtained a p-value of 0.000 (p<0.005), which suggests that there is an influence of application-based discharge planning on the levels of depression, anxiety, and stress in stroke patients.